Moisture & Acetaminophen analysis on the Aquilaria Malaccensis dried leaves extract - Alwi, Habsah; Syaira Kamaruddin, Nor; Jaafar, Jefri; Zainal Abidin, Hanafiah; Halim Ku Hamid, Ku (International Journal of Engineering and Technology, 2018)
Aquilaria malaccencis is a traditional herbal that has been long used in medicinal remedies due to its various health benefits.  Acetaminophen is a synthetic drug often used to treat fever and other illness and this compound can be found in Aquilaria malaccencis leaves.  In this work, the presence of acetaminophen was evaluated by drying the leaves at various temperatures (30- 70°C) using a fabricated vacuum far-infrared dryer.  The dried leaves were then extracted using hydro distillation method to produce essential oil. The presence of acetaminophenin in the extracted sample was confirmed by using FITR. A peak at 1640 cm-1 region indicated that carbonyl vibration infrared band in the spectrum of acetaminophen was observed for all three of the extracted samples. This confirmed the presence of acetaminophenin aquilaria malaccencis leaves.